Improving Students’ Writing Ability Through Team Assisted Individualization (TAI) Technique At Grade VIII.B of SMPN 2 Wawotobi - Umar Umar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research is aimed to improve students’ writing ability through Team Assisted Individualization (TAI) technique at grade VIII.B of SMPN 2 Wawotobi, in language use and organization aspect. The research question in the research as follows: ‘How to improve students’ writing ability through Team Assisted Individualization Technique at grade VIII.B of SMP Negeri 2 Wawotobi?’ and ‘Can Team Assisted Individualization Technique improve students’ writing ability at grade VIII.B of SMP Negeri 2 Wawotobi?’. This research took the design of classroom action research because it aimed at improving the existing condition in carrying out this research, the researcher acted as the teacher and the English teacher of SMPN 2 Wawotobi acted as an observer. Design of this research was an action research where this research was carried out in two cycles containing of four steps such as planning, action, observation and reflection. The subject of the research was all students of Grade VIII.B which consist of 25 students: 13 females and 12 males who registered in the academic year 2016/2017. The data were collected through third research instruments: writing test, observation sheet, and field note. All of the data were analyzed: quantitatively and qualitatively, and the result of the analysis was compared to the criteria of success defined in this research to see whether yes or not they were achieved. The target of the research was students comprehended the writing if minimally 75% of them got standard score 70. The result of the research shows that Team Assisted Individualization (TAI) technique could improve the students’ writing ability. It indicates that students at Grade VIII.B of SMPN 2 Wawotobi achieve the target on cycle II. It means that students’ writing ability in language use and organization aspect can improve by using Team Assisted Individualization technique. In the cycle I, students who get standard score ≥ 70 only 10 students (40%). It means that it do not get standard indicator of successfulness. Then researcher continues the research at the cycle II for get standard indicator of successfulness. In the cycle II, students who get standard score ≥ 70 were 20 students (80%). It means that they get standard indicator of successfulness. This result indicates that Team Assisted Individualization Technique can improve students’ writing ability on language use and organization aspects.